Polyketone-polypropylene core-shell fibers for concrete reinforcement (2024)
Corrosion of commonly used steel reinforcements weakens the structural strength of concrete. To address this issue, research was conducted on concrete reinforcements in the form of polymer fibers. These polymer fibers need concrete bonding ability and good mechanical properties. This study investigates core-shell fibers produced from polyketone and polypro pylene mixed with a compatibilizer. The core-shell fibers were produced by coextrusion and drawing. The fibers were analyzed by tensile tests, a single fiber pull-out test, contact angle measurements, scanning electron microscopy, and thermogravimetric analysis.